2023
DOI: 10.1136/tc-2022-057750
|View full text |Cite
|
Sign up to set email alerts
|

Smoke-free law compliance and predictive factors in Ethiopia: observational assessment of public places and workplaces

Abstract: ObjectivesThe primary objective of this observational study was to assess the status of public place and workplace compliance with smoke-free provisions in Ethiopia.MethodsThis study was conducted in four regions of Ethiopia (Oromia; Sidama; Harari; and Southern Nations, Nationalities, and Peoples’ Region) from September to October 2021. Data were collected using a standardised smoke-free checklist. Χ2tests were used to assess the association between categorical variables and the smoke-free status. Multivariab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In this meta-analysis, 25,573,329 study participants were involved. Five of the included studies focused on healthcare facilities ( 19 , 34–37 ), sixteen studies ( 14–17 , 21–27 , 29–31 , 33 , 38 ), one study on education sector ( 38 ), and one study on food and drinking service establishment ( 32 ). All of the included studies followed cross-sectional study design.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this meta-analysis, 25,573,329 study participants were involved. Five of the included studies focused on healthcare facilities ( 19 , 34–37 ), sixteen studies ( 14–17 , 21–27 , 29–31 , 33 , 38 ), one study on education sector ( 38 ), and one study on food and drinking service establishment ( 32 ). All of the included studies followed cross-sectional study design.…”
Section: Resultsmentioning
confidence: 99%
“…From the included studies, the highest non-compliance with smoke-free law was found to be 98.2% in food and drinking establishments ( 32 ) and the lowest non-compliance was 10.3% in healthcare facilities ( 36 ). Regarding the study country, four studies were conducted in India ( 29 , 31 , 35 , 37 ), two in China ( 17 , 30 ), two in Russia ( 28 , 38 ), one in United states ( 15 ), one in Guatemala ( 24 ) one in Indonesia ( 16 ), two in Ethiopia ( 14 , 36 ), two in South Africa ( 23 , 32 ), one in Australia ( 19 ), one in Portugal ( 34 ), one in European Union ( 27 ), one in Bangladesh ( 26 ), one in Vietnam ( 33 ), one in Turkey ( 22 ), one in Pakistan ( 21 ), and one in Nepal ( 25 ). Among the included the studies, the sample size ranged between 25,475,032 ( 15 ) and 40 ( 37 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Less than a third of countries with smokefree policies provide the necessary funding to enforce the policy, undermining their effectiveness. For example, in Ethiopia, which has nominally achieved the highest level of smokefree policy according to the WHO Report, compliance is low; according to one observational study, only 12.3% of sites visited were fully compliant with the smokefree law [ 8 ].…”
mentioning
confidence: 99%